ARCHITECTURE FOR INTEGRATING AIR QUALITY DATA FROM MULTIPLE SOURCES (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Air quality (AQ) monitoring has become an imperative component of public health strategy, yet traditional monitoring paradigms need improvement, and legacy systems designed for specific regional compliance struggle to keep up with the complexity of the problem. The study of existing air quality data reveals a variety of sources, data formats, and diverse parameter definitions across data providers. This paper proposes an architectural blueprint for a layered system capable of integrating air quality data, streamlining access to data from multiple sources into a single location, and reducing data heterogeneity to a common ground. The solution presented is implemented as an iOS software development kit (SDK) to demonstrate its practicality, with the long-term objective of transforming a disparate data landscape into a cohesive platform.
Keywords: Data integration; Air quality monitoring; Multi-source data; Data heterogeneity; Software development kit (SDK) architecture